The clash of civilizations? : the debate (New York : Foreign Affairs, 1996)
The clash of civilizations? The summoning. The dangers of decadence. The case for optimism. Civilization grafting. The modernizing imperative. Do civilizations hold? The West is the best.
Keywords: Politics; United States; International relations; World politics -- 20th century; United States -- Foreign relations -- 20th century